Are there competition issues associated with fake news during COVID-19? - Rakić, Ivana Ž. (Sociološki pregled, 2020)
Fake news is getting more attention because of the Internet and the rise of the online platforms and social networks, particularly in the age of COVID-19. Its sudden popularization creates important issues regarding how this phenomenon affects the society and democracy, as well as the consumers, competition and market. The question is what happens when fake news are spread (online) and misused during pandemic – whether to apply the European Union competition law in such cases? The author considers that European Commission should not deal with fake news challenges in the context of potential anticompetitive conducts. It is pointed out that fake news problem is not a competitive problem because the struggle against fake news is about the content not the competition and market power.